Potencial de remoção dos poluentes atmosféricos por arbustos urbanos: um estudo de microescala na cidade de São Paulo - Nascimento, Ulisses Lírio do (2021)
As a result of uncontrolled anthropogenic actions, urban areas experience problems related to air pollution, mainly arising from vehicular emissions. Problems at different scales and scenarios within the same city, which affect health and the local environment in different ways. Understanding the existence of pollutants in urban microenvironments combined with passive mitigation techniques enables urban resilience on a microscale. The objective of this work was to verify the existence and concentration levels of Carbon Monoxide (CO), Carbon Dioxide (CO2), Ozone (O3), Sulfur dioxide (SO2), Particulate Material (MP10) and (MP2, 5), Nitric Oxide (NO) and Nitrogen Dioxide (NO2), of vehicle origin, in the North terminal of the Companhia Paulista de Trens Metropolitanos (CPTM) in Tatuapé on a microscale by Equivalent Method. Propose a sustainable alternative for the mitigation of pollutants and indicate the potential that a green infrastructure has as a barrier and filter for these contaminants. In order to understand the potential that a green infrastructure has to act as a barrier and filter for contaminants, computational modeling was carried out with the I-TREE CANOPY program, projecting a green roof with shrubs, over the entire coverage of the CPTM station in Tatuapé and its North and South terminals. After analysis, the presence and concentrations of pollutants were identified: CO 631ppm, CO2 4.573ppm, O3 59μg/m3, MP10 1.398μg/m3, MP2.5 403μg/m3, and the pollutants NO, NO2 and SO2 did not show significant concentrations . It was also verified that the potential of urban shrubs to act as a natural barrier to contaminants arising from vehicle emissions are: Approximately 25 tons of CO2eq per year, and for other pollutants: 5.62 Kg of CO; 30.67 kg of NO2; 305.55 kg of O3; 19.32 kg of SO2; 14.85 kg of MP2.5; 102.35 kg of PM10 annually in an area of 25 thousand square meters. Within the conditions analyzed, this study concluded that there are atmospheric contaminants in the air at the Tatuapé Norte terminal and that the concentrations of CO, CO2, O3 and MP are above those recommended by the Environmental Company of the State of São Paulo (CETESB) and by the World Organization of Health (WHO), and the presence and concentrations of NO, NO2 and SO2 are below the tolerance limits and urban shrubs have the potential to act as a natural barrier to contaminants from vehicle emissions.